European Carbon Uptake has Not Benefited From Vegetation Greening. Issue 20 (14th October 2021) - Liu, Xuebang; He, Bin; Guo, Lanlan; Huang, Ling; Yuan, Wenping; Chen, Xiuzhi; Hao, Xingming; Xie, Xiaoming; Zhang, Yafeng; Zhong, Ziqian; Li, Tiewei; Chen, Aifang
Abstract: Substantial evidences indicate a widespread increase in European vegetation greenness since the 1980s due to CO2 fertilization effects (eCO2 ) and climate warming, but the impact of this process on the regional terrestrial carbon cycle has not been systematically evaluated. Using empirical models based on eddy covariance and process‐based models, we found that the widespread greening did not contribute to an increase in European carbon uptake (decrease in net ecosystem exchange) with a non‐significant trend from 2000 to 2018. The greening‐associated increase in gross primary productivity (GPP) is offset by the simultaneous increase in ecosystem respiration (TER). Moreover, frequent heatwaves cause stronger reductions in GPP than TER, preventing the increase of carbon uptake. These results reveal the double‐edged sword effect of warming on European ecosystems and will help constrain regional models. Plain Language Summary: In the past decades, elevating CO2 concentration and rising temperature have promoted the photosynthesis of European vegetation, thus increasing the greenness of vegetation. However, whether these processes could promote the ability of terrestrial ecosystems to absorb CO2 still lacks systematic evaluation. By using a variety of advanced vegetation dynamic models, we found that enhanced vegetation growth which absorbed more CO2, but also an enhancement of ecosystem respiration which released more CO2 in Europe during 2000–2018. The offsetting effect of these two processes has resulted in non‐significant trend in the European net CO2 uptake. In addition, the extremely high temperature events (heatwaves) frequently occurred in Europe in recent years, which have caused vegetation damage or even death, triggered forest fires, etc., thereby severely inhibited the carbon sink capacity of the terrestrial ecosystem. Key Points: CO2 fertilization effect and climate warming have led to greening of Europe, but it has not promoted an increase in ecosystem carbon uptake The increase in gross primary productivity related to greening is offset by the increase in ecosystem respiration Frequent European heatwaves also caused significant losses in the regional ecosystem carbon uptake